2018
DOI: 10.1111/jne.12632
|View full text |Cite
|
Sign up to set email alerts
|

Developmental programming of the female neuroendocrine system by steroids

Abstract: Developmental programming refers to processes that occur during early life that may have long-term consequences, modulating adult health and disease. Complex diseases, such as diabetes, cancer and cardiovascular disease, have a high prevalence in different populations, are multifactorial, and may have a strong environmental component. The environment interacts with organisms, affecting their behaviour, morphology and physiology. This interaction may induce permanent or long-term changes, and organisms may be m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…In this regard, it has been shown that altered patterns of DNA methylation and impaired gene expression of steroidogenic genes, among others, could be responsible for maternal hyperandrogenism that may affect the fetus during in utero life leading to developmental programming effects (Filippou & Homburg, 2017). The hypothesis of the developmental origins of PCOS by prenatal androgen exposure (Abbott et al, 2002) is widely supported by different animal models, including monkeys, sheep, and rodents (reviewed in Abruzzese et al, 2018; Stener‐Victorin et al, 2020). Moreover, evidence from patients has also shown that pregnant PCOS women present hyperandrogenism, increased AMH levels and altered CYP19 (aromatase) placental expression (Maliqueo et al, 2013; Sir‐Petermann et al, 2002; Tata et al, 2018).…”
Section: Pcos Pathogenesis and Association With Exposure To Endocrine...mentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, it has been shown that altered patterns of DNA methylation and impaired gene expression of steroidogenic genes, among others, could be responsible for maternal hyperandrogenism that may affect the fetus during in utero life leading to developmental programming effects (Filippou & Homburg, 2017). The hypothesis of the developmental origins of PCOS by prenatal androgen exposure (Abbott et al, 2002) is widely supported by different animal models, including monkeys, sheep, and rodents (reviewed in Abruzzese et al, 2018; Stener‐Victorin et al, 2020). Moreover, evidence from patients has also shown that pregnant PCOS women present hyperandrogenism, increased AMH levels and altered CYP19 (aromatase) placental expression (Maliqueo et al, 2013; Sir‐Petermann et al, 2002; Tata et al, 2018).…”
Section: Pcos Pathogenesis and Association With Exposure To Endocrine...mentioning
confidence: 99%
“…In accordance with this, one of the most accepted animal models of PCOS is the intrauterine androgen excess model. In this animal model, pregnant females are exposed to high androgens levels through testosterone or DHT injections during different periods of pregnancy (reviewed in Abruzzese et al, 2018). By using these animals' models, metabolic, endocrine and reproductive outcomes have been studied in the Filial 0 (exposed animals) and their offspring (Filial 1, F1); however, there are only few studies that focused on the subsequent generations (Figure 6).…”
Section: Pregnancy and Offspring Outcomes In Pcosmentioning
confidence: 99%
See 1 more Smart Citation
“…The cellular pathways mediating rapid glucocorticoid signalling in negative feedback effects are also discussed. The effects of steroids and endocrine disruptors during development and their long‐term consequences are extensively discussed in the review by Abruzzese et al Last but not least, the review by Avalos et al discusses the involvement of hypothalamic epigenetic mechanisms in the control of energy homeostasis and feeding behaviours.…”
mentioning
confidence: 99%
“…According to Moreira et al (2019), fetal programming is a concept that encompasses adaptation mechanisms in which nutrition during the gestational period and the uterine environment influence fetal development, which can lead to permanent phenotypic changes in the progeny. However, the concept of fetal programming goes beyond just nutritional stimuli, being pointed out in several studies as any process that has an influence on the pregnant female and can have consequences for the fetus and in the long term in the progeny (BARKER et al, 1993;LUCAS;FEWTRELL;COLE, 1999;ABRUZZESE et al, 2018).…”
Section: Introductionmentioning
confidence: 99%